Europe's future depends on perspective not policy. Issue 3 (September 2020) - Kuus, Merje
Before we can fruitfully discuss what Europe ought to do about its various policy dilemmas, we need to re-examine the lens through which we view these dilemmas. I will highlight two problems with the habitual lens on Europe's future: firstly, it's unrealistic emphasis on clarity and coherence and, secondly, its state-centrism and state-envy. I explore the ways in which we can reverse the lens to examine familiar problems from unfamiliar angles.